Bridging the Visegrad Group and East Asia Through Cooperation - Laš, Lukáš (Overcoming Controversies in East Asia, 2017)
The re-emergence of East Asia brought more interactions of Asian capital and peoples with the countries of the Visegrad Group (V4). China, the Republic of Korea, Japan have a history of relations with Czechia, Hungary, Poland, and Slovakia. The moderate discovering of Asia by the V4 in the last decade is being substituted by growing Central European governmental initiatives to attract capital, products, tourists, and to cultivate cooperation with East Asia. The paper is devoted to a review of Visegrad–East Asia relations with a focus on trade cooperation. Its goals are to reflect on current trends and to popularize the Visegrad brand of the EU in Asia.